Basal renal function in paediatric patients: Correlation of methods that depend on a 24 h urine collection with simpler methods that do not require a timed urine - Mercedes Ubetagoyena Arrieta; Ramón Areses Trapote; Jone Mendia Ubetagoyena; Marisol Perez Revuelta; Irati García Albizua (Elsevier, 2020)
Introduction: In the daily practice it is necessary to have quick, easy and accesible methods to adequately assess the renal function. The objectives were: 1. Quantify the relationship and concordance of the glomerular filtration rate (FG) calculated by the clearance of creatinine in 24 h urine (CCr) and the original and modified Schwartz equation (SE). 2. Correlate urine elimination of substances that depend on the volume of excreted urine in a unit of time with other parameters that are calculated measuring the concentration of these substances in blood and urine. Materials and methods: The study included 401 healthy children in the ages between 3 to14 (187 male and 214 female). The analysis between the variables was carried out by Pearson's correlation coeficient and the intraclass correlation coefficient. Results: The correlation between values of CCr and the original SE (non standardized creatinine measuring) was r = 0.58 (P < 0.001) and the concordance, CCI = 0.74. Correlation between values of CCr and the modified SE (standardized creatinine measuring) was r = 0.68 (P < .001) and the concordance CCI = 0.78. There is a very significant correlation between the elimination of sodium in 24 h urine (mEq/Kg/24 h) and the Na-Fractional-Excretion (EFNa): r = 0.8 (P < .001). There was a correlation between the potasium elimination in 24 h (mEq/Kg/24 h) and EFK: r = 0.85 (P < .001). Between volume/minute/1.73 m² and the urine volume for each 100 ml FG was: r = 0.88 (P < .001). Conclusions: These equations provide valuable information of the state of the basal renal function without having to turn to the minuted urine. Resumen: Introducción: En la práctica diaria es necesario disponer de métodos rápidos, sencillos y accesibles para valorar adecuadamente la función renal. Los objetivos fueron: 1) Cuantificar la relación y concordancia de la tasa de filtración glomerular (FG) calculada mediante el aclaramiento de creatinina en orina de 24 h (CCr) y la fórmula de Schwartz (FS) original y la FS modificada. 2) Relacionar la eliminación urinaria de sustancias que dependen del volumen de orina expulsada en una unidad de tiempo con otros parámetros que se calculan midiendo la concentración de estas sustancias en sangre y en orina. Material y métodos: El estudio incluyó 401 niños sanos de 3-14 años (187 hombres y 214 mujeres). El análisis entre las variables se realizó mediante el coeficiente de correlación de Pearson y el coeficiente de concordancia interclase tipo consistencia. Resultados: La correlación entre los valores de CCr y FS original (medición de creatinina no estandarizada) fue r = 0,58 (p < 0,001) y la concordancia (CCI = 0,74). La correlación entre las cifras de CCr y FS modificada (medición de creatinina estandarizada) fue r = 0,68 (p < 0.001) y la concordancia CCI = 0,78. Existía una correlación muy significativa entre la eliminación de sodio en orina de 24 h (mEq/Kg/24 h) y la Excreción-Fraccional-Na (EFNa): r = 0,8 (p < 0,001). También entre la eliminación de potasio en 24 h (mEq/Kg/24 h) y EFK: r = 0,78 (p < 0,001). Entre la proteinuria (mg/m²/hora) y el cociente proteína/creatinina urinario: r = 0,85 (p < 0,001). Y entre el volumen urinario (ml/minuto/1,73 m²) y el volumen por cien FG r = 0,88 (p < 0,001). Conclusiones: Estas ecuaciones proporcionan una valiosa información del estado de la función renal basal sin tener que recurrir a la orina minutada.